Prostate cancer-associated lncRNAs. (1st April 2018) - Mitobe, Yuichi; Takayama, Ken-ichi; Horie-Inoue, Kuniko; Inoue, Satoshi
Abstract: Long non-coding RNA (LncRNA) is defined as an RNA transcript that does not encode any protein, with a length longer than 200 nt. Based on the recent advances in high-throughput sequencing techniques, a large number of lncRNAs have been characterized as functional transcripts that play important roles in various biological processes as well as pathologic states. In a research field of prostate cancer, several key lncRNAs have been identified as new players that contribute to the pathophysiology of the disease, which is primarily regulated by androgen and its cognate receptor. This review sheds light on the history and future perspective of these prostate cancer-associated lncRNAs. Highlights: LncRNAs contribute to the pathophysiology of prostate cancer (PC). PC-associated lncRNAs exert actions through modulating their binding partners. PC-associated lncRNAs associate with progression and therapy resistance of PC. Several PC-associated lncRNAs could be context-dependent in cancers. LncRNAs can be targets for diagnosis and therapy of PC.